Community Peace Asset Mapping: Rereading Our World, Rereading Ourselves - Robin Neustaeter (Adult Education Research Conference, 2007)
Peace education critically confronts violence in our society and develops peace practices and theories, at the local, national, and global levels. This interactive session will critically explore the concepts and questions linking peace education and lifelong learning to deconstruct dominant social values that perpetuate violence.